2006
DOI: 10.2174/138955706776073484
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperglycemic Potential of Natural Products

Abstract: In order to evaluate the anti-hyperglycemic effect of natural compounds via the inhibition of alpha-glucosidase (AGH), the potential inhibitory effect of anthocyanins, caffeic acid analogs, and caffeoylquinic acid analogs have been reviewed. A new AGH assay system to mimic the membrane-bound AGH at the small intestine was proposed and evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 32 publications
6
103
0
2
Order By: Relevance
“…Another study showed that acarbose is a good inhibitor for α-glucosidase [26]; our experiment showed similar results and inhibition capacity for α-amylase. Type-I α-glucosidase, derived from yeast, is usually of higher purity, while α-glucosidase, derived from rat small intestine, Type-II, mimics mammals more [27]. Inhibition ability of acarbose for type-II α-glucosidase is superior to that of type-I [17]; similar results were found in our experiment.…”
Section: Discussionsupporting
confidence: 88%
“…Another study showed that acarbose is a good inhibitor for α-glucosidase [26]; our experiment showed similar results and inhibition capacity for α-amylase. Type-I α-glucosidase, derived from yeast, is usually of higher purity, while α-glucosidase, derived from rat small intestine, Type-II, mimics mammals more [27]. Inhibition ability of acarbose for type-II α-glucosidase is superior to that of type-I [17]; similar results were found in our experiment.…”
Section: Discussionsupporting
confidence: 88%
“…We assayed the ␣-glucosidase by the free enzyme system while Matsui et al (8) used the immobilized enzyme system developed by Oki et al (14). The significance of these two assay methods was discussed in a review article by Matsui et al (15).…”
Section: Discussionmentioning
confidence: 99%
“…Há necessidade premente de se explorar o campo da fitomedicina para fornecer terapias alternativas no tratamento da síndrome diabética (80). A comunidade científica tem grande interesse em avaliar o estado do produto natural isolado em estudos experimentais, sendo que alguns deles já foram testados em seres humanos (81)(82)(83)(84).…”
Section: Pesquisa Translacional Em Dmg E Hgl Para Estudos De Intervençãounclassified